Sex differences in healthy human heart rate variability: a meta-analysis - Koenig, Julian; Thayer, Julian F. (Neuroscience & biobehavioral reviews, 2016)
The present meta-analysis aimed to quantify current evidence on sex differences in the autonomic control of the heart, indexed by measures of heart rate variability (HRV) in healthy human subjects. An extensive search of the literature yielded 2020 titles and abstracts, of which 172 provided sufficient reporting of sex difference in HRV. Data from 63,612 participants (31,970 females) were available for analysis. Meta-analysis yielded a total of 1154 effect size estimates (k) across 50 different measures of HRV in a cumulated total of 296,247 participants. Females showed a significantly lower mean RR interval and standard deviation of RR intervals (SDNN). The power spectral density of HRV in females is characterized by significantly less total power that contains significantly greater high- (HF) and less low-frequency (LF) power. This is further reflected by a lower LF/HF ratio. Meta-regression revealed significant effects of age, respiration control and the length of recording available for analysis. Although women showed greater mean heart rate, they showed greater vagal activity indexed by HF power of HRV. Underlying mechanisms of these findings are discussed.
Gesehen am 29.04.2020